1997
DOI: 10.1007/s002160050597
|View full text |Cite
|
Sign up to set email alerts
|

Determination of impurities in micro-amounts of silver alloys by electrothermal vaporization inductively coupled plasma mass spectrometry (ETV-ICP-MS) after in-situ-digestion in the graphite furnace

Abstract: Forgeries of antique silver objects can be identified by their fingerprints of impurities. The dissolution of the samples causes severe problems since Au and Ag have to be dissolved simultaneously. In order to overcome that difficulty and to minimize the amount of sample, an ETV-ICP-MS method is presented based on solid sampling and an in-situ-digestion with nitric acid in a graphite tube. Determinations of Au, Bi, Cd, Pb, Sb, Sn and Zn were performed in a range of 10 µg/g-1 % and with an accuracy of 10%-50%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It is generally accepted that the use of ICP-MS as the detection system results in a higher influence of matrix effects, [17][18][19] making it more difficult to use external calibration with aqueous standards. However, it can be noticed that here also the first papers published on this topic usually recommended the use of external calibration with solid materials, [20][21][22][23] while in later papers solution-based calibration procedures have been proposed (including internal standardization, single standard addition and isotope dilution), 5,6,[24][25][26][27][28][29] and even the simplest calibration approach (external calibration with aqueous standards) has proved to be successful on occasions as a better insight into the real possibilities of the method has enabled a reduction of the influence of matrix effects. 8,30,31 It is the purpose of this paper to critically compare the performance of solid sampling-ETV-ICPMS and solid sampling-GFAAS in an area in which both compete, fast and direct mono-element determination, since information on this point is very scarce.…”
Section: Introductionmentioning
confidence: 98%
“…It is generally accepted that the use of ICP-MS as the detection system results in a higher influence of matrix effects, [17][18][19] making it more difficult to use external calibration with aqueous standards. However, it can be noticed that here also the first papers published on this topic usually recommended the use of external calibration with solid materials, [20][21][22][23] while in later papers solution-based calibration procedures have been proposed (including internal standardization, single standard addition and isotope dilution), 5,6,[24][25][26][27][28][29] and even the simplest calibration approach (external calibration with aqueous standards) has proved to be successful on occasions as a better insight into the real possibilities of the method has enabled a reduction of the influence of matrix effects. 8,30,31 It is the purpose of this paper to critically compare the performance of solid sampling-ETV-ICPMS and solid sampling-GFAAS in an area in which both compete, fast and direct mono-element determination, since information on this point is very scarce.…”
Section: Introductionmentioning
confidence: 98%
“…Moor et al reported an ETV-ICP mass spectrometry technique based on solid sampling and in situ digestion with nitric acid in a graphite tube. 12 Several difficulties still remain, such as introducing small amounts of pre-weighed samples into the ETV device, removing the residues from it, and finding an accurate calibration method. To overcome these problems, we proposed the mechanical or magnetic drop-in techniques for sampling, an exchangeable furnace made of graphite or tungsten, and the use of standard iron plates for calibration.…”
Section: Introductionmentioning
confidence: 99%
“…Various ETV systems have been described. Regarding the analysis of metal samples, Moor et al 7 reported a unique ETV-ICP-MS method based on one-particle sampling and in situ digestion (or micro-digestion) with nitric acid in a graphite tube furnace. In their method, one particle of silver alloy sample was weighed accurately with an electronic microbalance.…”
Section: Introductionmentioning
confidence: 99%